การศึกษาเปรียบเทียบผลกระทบที่มีต่อเครื่องยนต์ขนาดเล็กเมื่อใช้น้ำมันปาล์มดิบและน้ำมันปาล์มโอเลอีน - พงษ์ภัทร พุกะนัดด์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The objectives of the study were comparing the engine performance, smoke emission, and engine durability when fueling with Crude Palm Oil (CPO) and Palm Olein on a small CI engine. Moreover, the study also monitored the changing of the lubricating oil conditions, contamination and metal wear conditions during the engine durability test. CPO in this study was heated to be 45±5 oC. The study was divided into two parts. The first part was comparing the engine performance, and smoke emission among using CPO, using Palm Olein, and using diesel. The performance study had found that the maximum torque of the engine using CPO and using Palm Olein were not significantly different from the maximum torque of engine using diesel while the specific fuel consumption, the exhaust temperature, and the smoke density of the engines using either CPO or Palm Olein were higher than diesel and not different to each other. The second part, to compare the effects on long term usage using a model of working cycle, was engine durability testing, of 320 working hours, between the engine fueling with CPO and the engine fueling with Palm Olein. The study had found that more working hours made the dropping of engine performance of the engine fueling with these three types of fuel. After the durability test, the performance of the engine fueling with diesel was slightly drop while the performance of the tested engine fueling with CPO was drop from new engine by 10% to 20%. The performance of the tested engine fueling with Palm Olein was drop from new engine by 5% to 14%. In addition, results of lubricating oil monitoring (only in the engine fueling with CPO) had showed the high level of silicon contamination in the lubricating oil that would make abnormal level of iron, chromium, and aluminum contamination. However, the engine fueling with CPO might have some abnormal wear phenomena. Moreover, some soot that stuck on the injector was found. It was noted that there were small amount of the soot in the engine fueling with diesel but the higher amount with Palm Olein and the highest amount with CPO. Because of the large amount of sticky soot of the engine fueling with CPO, the engine could possible be broken down especially the injector. The outcome of this study can be concluded that CPO needed to be heated before used. The engine fueling with CPO requires shorter maintenance duration from the typical diesel such as shorten the lubricating oil working hours or often clean the injector. In the other hand, the Palm Olein could be used as alternative fuel with more compatibility.